Kant, Jesuits and Catholicism - an historical perspective - Durán Casas, Vicente (Con-Textos Kantianos. International Journal of Philosophy, 2024)
It can be said that Kant’s philosophy has been considered a system of thought contrary to the philosophical and theological thought of Catholicism. But this has a more complex history that many are unaware of: in Germany there was a group of Catholic thinkers who, even during Kant’s lifetime, positively interpreted the Prussian’s ideas and believed they could integrate them into Catholic theology. But shortly after Kant’s death in Rome there was a non-academic and non-transparent process to exclude the possibility of a fruitful dialogue between Kant and Catholic thought, and as a consequence of that the Critique of Pure Reason was included in the Index Librorum Prohibitorum and this initial dialogue was thus prevented from continuing. However, in the 20th century there were outstanding Catholic thinkers, philosophers and theologians, some of them prominent Jesuit intellectuals, who in fact assumed the methods and conclusions of Kant’s transcendental philosophy and thereby opened Catholic theology to a very fruitful dialogue with the central ideas of critical philosophy of Kant. In the text “Kant, Jesuits and Catholicism - an historical perspective” - I briefly tell the story of a complex but still fruitful relationship.